The Emergence of Viral Encephalitis in Donkeys by Equid Herpesvirus 8 in China - Wang, Tongtong; Hu, Leyu; Liu, Mengyuan; Wang, Tianjiao; Hu, Xinyao; Li, Ying; Liu, Wenqiang; Li, Yubao; Wang, Yonghui; Ren, Huiying; Zhang, Wei; Wang, Changfa; et al. (Frontiers in Microbiology, 2022)
The equine herpesvirus type 8 (EHV-8) can cause significant economic losses in the global horses and donkey industry. The disease has been associated with abortion and respiratory symptoms. However, rare study was reported about donkeys with neurological diseases induced by EHV-8 infection. In the present study, one 2-years old male donkey died with a severe neurological disorder from a large-scale donkey farm in China. The causative agent, donkey/Shandong/10/2021 (GenBank accession: OL856098), was identified and isolated from the brain tissue of dead donkey. Meanwhile, BALB/c mice were used as an animal model to evaluate EHV-8 isolate pathogenicity. Our data showed that EHV-8 was positive in brains by PCR and IHC, which induced typical viral encephalitis lesions in both donkey and mice consistent with clinical signs. For the first time, we reported that EHV-8 had been isolated from donkeys with neurological illness in China, which is helpful to reveal the pathogenicity of EHV-8 in the donkey.